Multilevel Analysis: Biopsychosocial Determinants and Environmental Factor on the Incidence of Diarrhea Among Children Under Five in Surakarta - Erick Zicof; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2018)
Background: Diarrhea is an endemic disease with a potential to become an epidemic in Indonesia. Diarrhea most often occurs in children under five years of age. This study aimed to determine the relationship between biopsychosocial factors, environmental factor, and diarrhea occurrence in Surakarta, Central Java, using multilevel analysis.Subjects and Method: This was an observational analytic study with a cross-sectional approach. This study was conducted on October 2017 - April 2018. A sample of 200 children under five years of age was selected by fixed disease sampling, consisting of 100 children with diarrhea and 100 without diarrhea. The dependent variable was the incidence of diarrhea. The independent variables were the number of family members, maternal knowledge, maternal personal hygiene, and environmental sanitation. The data were collected by questionnaire and analyzed by multilevel logistic regression in Stata 13.Results: The number of family member (b= 1.09; 95% CI= 0.02 to 2.15; p< 0.046) increased the risk of diarrhea. Good maternal knowledge (b= -2.30; 95% CI= -3.46 to -1.14; p<0.001), good maternal personal hygiene (b= -2.09; 95% CI= -3.48to-0.70; p<0.003), and good environmental sanitation (b= -1.64; 95% CI= -2.84to -0.43; p= 0.008) decreased the risk of diarrhea in children under five. The village had a substantial contextual effect on the incidence of diarrhea with ICC= 66.14%.Conclusion: The number of family member increases the risk of diarrhea. Good maternal knowledge, good maternal personal hygiene, and good environmental sanitation decrease the risk of diarrhea in children under five. Village has a substantial contextual effect on the incidence of diarrheaKeywords: diarrhea, number of family member, maternal knowledge, maternal personal hygiene, village, contextual effectCorrespondence: